Protective role of endothelial progenitor cells stimulated by riociguat in chronic thromboembolic pulmonary hypertension. (15th January 2020) - Yamamoto, Keiko; Nishimura, Rintaro; Kato, Fumiaki; Naito, Akira; Suda, Rika; Sekine, Ayumi; Jujo, Takayuki; Shigeta, Ayako; Sakao, Seiichiro; Tanabe, Nobuhiro; Tatsumi, Koichiro
Abstract: Background: Pulmonary endothelial damage has a negative impact on the maintenance of normal pulmonary vascular function. Such damage results in delayed thrombus dissolution and vascular remodeling in chronic thromboembolic pulmonary hypertension (CTEPH). Although endothelial progenitor cells (EPCs) may be incorporated into neovasculature during vascular repair, their function in CTEPH remains unclarified, especially under the augmentation of soluble guanylate cyclase (sGC) activity. Methods and results: We evaluated the effect of EPCs on endothelial function and compared the effect of riociguat, a sGC stimulator, on the number and function of circulating EPCs in two groups of CTEPH patients. The two groups consisted 16 CTEPH patients who were treatment naïve (Naïve group), and 14 CTEPH patients who were being treated with riociguat, a sGC stimulator (Riociguat group). The number of circulating EPCs in the Riociguat group was significantly higher than that in the Naïve group. Gene expression levels associated with angiogenesis were significantly higher in EPCs of the Riociguat group. EPC-stimulated tube formation and migration of human pulmonary microvascular endothelial cell (hPMVEC) in the Riociguat group exceeded that in the Naïve group. The angiogenic ability of hPMVECs stimulated by EPCs in the Riociguat group was enhanced compared to that of the sGC stimulator, BAY 41–2272. Conclusion: These findings indicate that riociguat may induce EPCs to play a protective role via modulation of endothelial functions associated with CTEPH. Translation aspect of the work: Endothelial dysfunction exacerbates CTEPH. Riociguat enhanced the protective role of EPCs via neovascularization, which prevented vascular remodeling and alleviated CTEPH. Highlights: The number of circulating EPCs increased in CTEPH patients treated with riociguat. Riociguat increased tube formation and hPMVEC migration more than BAY 41–2272. Findings suggest that EPCs of CTEPH patients taking riociguat play a protective role.